Penerapan Literasi Numerasi Dengan Model Pembelajaran Homeschooling - Chandra; Sunter Candra Yana (Institute of Computer Science (IOCS), 2022)
Literacy as a 21st century life skill through integrated education. Numerical literacy skills are explicitly taught in mathematics, but students are given various opportunities to use mathematics outside of mathematics, in a variety of situations. Using math skills across curriculum will enrich learning in other subject areas and contribute to broadening and deepening understanding of numeracy. The method used in this research uses a descriptive method with a qualitative approach, because the researchers consider this research system to be most related to the problems studied about Homeschooling. Homeschooling is an alternative model of education that is carried out in a family manner in order to be able to find out and develop the potential abilities of children. In the application of home schooling, parents are also fully responsible for the development of children in exploring children's interests and talents, what they like from the material being studied, and so on. Homeschooling can be done flexibly, meaning that it can be done anywhere, anytime, and by anyone. However, Homeschooling can be done flexibly, but in this case there is also a negative impact from Homeschooling, namely if parents also do not take part in the implementation of Homeschooling because parents are an essential factor in the implementation of Homeschooling.